Ising spins on discrete Regge lattices - Bittner, Elmar; Janke, Wolfhard; Markum, Harald; Riedler, Jürgen (Physica. A, Statistical mechanics and its applications, 2000)
We study an Ising spin system coupled to the fluctuating two-dimensional geometry of the discrete Regge model and compare with the results of the standard Regge calculus. Particular emphasis is placed on the phase transition of the spin system and the associated critical exponents. The results are obtained from finite-size scaling analyses of extensive Monte Carlo simulations.